Effect of Shrimp Oil-Based Simulated Fat on Flavor and Physical Properties of Shrimp Surimi Products - GUO Yuchen, HUANG Jinyan, ZHAO Yuan, SHI Linfan, REN Zhongyang, WENG Wuyin (Shipin Kexue)
In this study, the effect of shrimp oil-based simulated fat on the flavor and physical properties of shrimp (Litopenaeus vannamei) surimi products was investigated. The sensory evaluation results showed that the smell and taste scores of surimi products increased with the increase in simulated fat content. By gas chromatography-ion mobility spectrometry (GC-IMS), a total of 30 volatile organic compounds were identified in shrimp surimi products with simulated fat, and the contents of ketones and esters increased with the increase in simulated fat content. The highest hardness and gel strength of 2 472.04 g and 826.14 g·mm, respectively were obtained when the simulated fat content was 4.0%. Confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM) showed that when added at 4.0%, the simulated fat was evenly distributed in the dense gel network of surimi products. Therefore, adding an appropriate amount of shrimp oil-based simulated fat can not only enhance the sweet flavor of shrimp surimi products, but also improve its gel properties. The results of this study can provide a theoretical basis for the quality improvement of shrimp surimi products.